Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s00134-013-3037-2
|View full text |Cite
|
Sign up to set email alerts
|

The PRESERVE mortality risk score and analysis of long-term outcomes after extracorporeal membrane oxygenation for severe acute respiratory distress syndrome

Abstract: The PRESERVE score might help ICU physicians select appropriate candidates for ECMO among severe ARDS patients. Future studies should also focus on physical and psychosocial rehabilitation that could lead to improved HRQL in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
510
12
11

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 477 publications
(585 citation statements)
references
References 51 publications
(91 reference statements)
36
510
12
11
Order By: Relevance
“…Recently, several predictive mortality risk scores to help clinicians target the patients most likely to benefit from ECMO have been proposed 18, 21, 22. Among these, age9, 18, 21, 22, 23, 24 and SOFA score21, 22, 23, 24 were found to be particularly closely associated with hospital mortality and were independent prognostic factors in ARDS patients receiving ECMO support.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several predictive mortality risk scores to help clinicians target the patients most likely to benefit from ECMO have been proposed 18, 21, 22. Among these, age9, 18, 21, 22, 23, 24 and SOFA score21, 22, 23, 24 were found to be particularly closely associated with hospital mortality and were independent prognostic factors in ARDS patients receiving ECMO support.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when no improvement was observed after 5 days, ECMO was stopped, which prevented any possibility of late clinical improvement. Thirdly, the patients were included in the trial after prolonged mechanical ventilation and it was demonstrated that the deaths of patients who had received ECMO support was strongly associated with the number of days of mechanical ventilation before installation of the device [3]. Indeed, the benefit anticipated with that new technique was to rapidly ensure rest for the lungs due to the highly protective ventilation, before the disease could evolve towards destructive fibrosis.…”
Section: Randomized Trials Of Ecmo In Ards Patientsmentioning
confidence: 99%
“…It must also be emphasized that the most recent studies reported mortality rates for patients with the most severe forms of ARDS, defined as hypoxemia or hypercapnia refractory to initial management and treated conventionally, exceeding 60% [1][2][3]. The results of the first randomized trial were disappointing, but it should be noted that it took place many years ago, when the technology was in its infancy.…”
Section: Why a New Trial Now?mentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, factors strongly associated with poorer outcomes in series of severe ARDS patients receiving ECMO were older age, a greater number of days of MV before ECMO, a higher number of organ failures, low pre-ECMO respiratory system compliance, absence of paralysis or prone positioning before ECMO, and immunosuppression [15,16]. Based on these factors, predictive survival models have been developed to help clinicians select appropriate candidates for ECMO.…”
Section: Why Should Ecmo Be Initiated Rapidly In This Patient?mentioning
confidence: 99%